Decision Making and the Limits of Evidence: A Case Study of Acute Stroke in Pregnancy. (April 2016) - Boyko, Matthew; Iancu, Daniela; Lesiuk, Howard; Dowlatshahi, Dar; Shamy, Michel C. F.
We report the case of a pregnant woman treated for acute ischemic stroke and review the literature on acute stroke treatment in pregnancy. To our knowledge, this is the first case reporting the successful use of intravenous tissue plasminogen activator and a stent retriever for acute stroke in pregnancy. We then use this case to consider the way medical knowledge is used in therapeutic decision making and argue that decision making necessarily extends beyond the limits of clinical trial evidence.